PERSEPSI PELAKU USAHA MIKRO KECIL DAN MENENGAH TENTANG AKUNTANSI, PENGETAHUAN AKUNTANSI, DAN SKALA USAHA TERHADAP PENGGUNA INFORMASI AKUNTANSI - Asih Purwo Kentari (JURNAL EKOBIS DEWANTARA, 2023)
This study aims to find out how important the perceptions of micro, small and medium enterprises actors are regarding accounting, accounting knowledge, and business scale to users of accounting information. The research method is carried out through literature study using national journals and international journals. The results of this study, micro, small and medium enterprises influence accounting knowledge and accounting information in developing a business.